Pengaruh Lama Waktu Biofermentasi Chromolaena odorata dengan Sumber Karbon Gula Lontar Cair Terhadap Kualitas Fisik - Yohana Hartati Nidi; Marthen Luther Mullik; Twen O. Dami Dato; Gustaf Oematan (Yayasan Sumber Daya Manusia Cerdas, 2023)
The purpose of this study was to determine the effect of the length of biofermentation time of Chromolaena odorata with a source of liquid palm sugar carbon on the physical quality content. The method used in this study is the Complete Randomized Design (RAL) method with 4 treatments and 4 repeats so that there are 16 experimental units. The treatment used is: LB0: biofermentation duration 0 days, LB7: biofermentation duration 7 days, LB14: biofermentation duration 14 days, LB21: as control. The results of variety analysis showed that biofermentation of Chromolaena odorata with liquid palm sugar carbon source had a real effect (P>0.05) on color, aroma, texture, pH and temperature, but did not have a real effect (P<0.01) on the presence of fungi. Based on the results of the study, it can be concluded that the length of biofermentation time of Chromolaena odorata with a source of liquid palm sugar carbon at a length of 14 days gives the best results for color, texture and temperature, the length of 7 days gives the best results for pH and smell while biofermentation with different times gives the same effect for the presence of fungi.